Basic Pedagogical Conditions of Forming Cognitive-Emotional Perception of Musical Works of Viennese Classics by the Future Teachers in the Process of Piano Learning - Tan Siyao (Pedagogical Discourse, 2017)
The perception process of art works is the basis for all artistic activity and is being examined concerning musical activity in particular and on the whole in the article. Student’s piano preparation can not be effective without forming cognitive and emotional perception of Viennese classics’s music works, as it is the basis for all piano studies of future specialists. The problem’s actuality is being predefined by the necessity of future teacher’s instrumental-conductive preparation and its efficiency increase due to the development of their general musical culture on the basis of capturing highly artistic and classic art works; also the creation of corresponding pedagogical terms related to cognitive and emotional perception’s start related to music works in this epoch.Under the noted pedagogical terms we understand such specially created terms as which are necessary and sufficient for understanding and recreation of music works in this epoch in the process of performance activity.Their creation consists both of student’s preparation for this activity and providing of necessary environment during the studies at university, which is: positive emotional atmosphere in the piano class, activization of professional dialog between teacher and student during studies, pedagogical stimulation of educational‑cognitive and independent student’s work. Noted terms assist the development of student’s interest for piano’s self-expression performance; the necessity’s activization in development of their own cognitive and emotional perception related to classic’s time music works.Their complex usage must provide the harmonious instrumental-performance student’s development where a process of artistic cognition is a co-operation of perception, evaluation and creation in art.We presented special pedagogic conditions on which occurs rise effectiveness of forming cognitive whith co-operation of perception music works of Viennese classic by future music teachers in the process of piano study. The process of forming student readiness to perception of classic music heritage is the main task of throughout the piano readiness of future specialists.